Проблеми імплементації європейських стандартів якості довкілля у водне законодавство України - Уберман, В. І.; Васьковець, Людмила Антонівна (Запорізький національний університет, 2020)
Досліджено перші кроки співробітництва України та ЄС з імплементації в українське водне законодавство базових еколого-правових категорій та визначень законодавства ЄС, зокрема стандарту якості довкілля для поверхневої води. Виявлено принципові відмінності у відповідних поняттях, причиною яких є різне спрямування законодавств ЄС та України: водоохоронне та господарське відповідно. Розглянуто еколого-правові наслідки відмінностей. Зроблено висновок, що усунення невідповідностей слід починати з рецепції зазначеного базового європейського поняття.

The article examines the problems that arise in the implementation in Ukrainian water legislation of key environmental and legal categories and concepts of EU legislation. The aim is to identify differences in the basic concepts of water legislation of the EU and Ukraine on environmental quality standards for determining the chemical status of surface waters. The article provides an analytical comparison of the concepts used in the Water Code of Ukraine (WCU) and bylaws with those contained in EU directives. The main object of research are the concept of “environmental quality standard” (EQS) from Directive 2000/60/EC, Directive 2008/105/EC and its counterparts in WCU. The fundamental difference between the concept of EQS and the similar concept “standard of maximum admissible concentration of pollutant” in the Ukrainian environmental legislation is revealed. Formally similar to EQS, the concept of “environmental standard of water quality” (ESWQ) was introduced in WCU as a result of the introduction of the European environmental and law institute of integrated water resources management on a basin principle. Methods and tools for using ESWQ to determine the state of waters are contained in a set of bylaws to the WCU. As a result of an analytical comparison of ESWQ and EQS, it was concluded that these concepts do not agree either in purpose or in form and manner of expression. The possibility to avoid the introducing of the concept of EQS in the WCU has been investigated. It is determined that the absence of the concept of EQS in the conceptual core of WCU distorts a clear water protection direction, which should be followed when approaching European water legislation. The following main conclusions are made. 1. There are fundamental differences between the basic concepts in water legislation of the EU and in Ukraine on determining the chemical status of surface waters, the reason for which is the different purpose of these laws: water protection and economic goals, respectively. 2. The lack of implementation of the EQS in its European meaning into the Ukrainian water legislation determines the divergent nature of European and Ukrainian water protection activity and law enforcement practice in this sphere. 3. The identified deep differences mean that the paradigm of Ukrainian water protection requires a change from economic direction to environmental one. 4. Greening of Ukrainian water legislation should begin with the priority reception of basic European concepts, which include EQS.
Problems of implementation of European environmental quality standards in water legislation of Ukraine
Keywords: водне законодавство; імплементація директив ЄС; базові визначення та поняття; забруднюючі речовини; якість води; water legislation; implementation of EU directives; basic definitions and concepts; pollutants; water quality